IMPLEMENTASI PRINSIP DEMOKRASI DAN NOMOKRASI DALAM STRUKTUR KETATANEGARAAN RI PASCA AMANDEMEN UUD 1945 - Martha Pigome (Faculty of Law, Universitas Jenderal Soedirman, 2011)
The principle of democracy and nomocracy as state in the Constitution 1945 is the embodiment of the state that based on civil sovereignty and state characteristics that uphold the law. Implemention of those two principles changes the structure of the state that established the Constitutional Court. This institution known as the guardian of democracy of any process of political democatization and legal policy. The consitutional Court plays an important role in maintaining the state constitution (Constitution 1945). Constitutional Court have an authority to solve dispute elections and general election. This institution also have a role to judicial review of any statute that not synchronize with the Constitution 1945. Keywords : Demoratization, Rule of Law, Constitution and Legal Policy